2007
DOI: 10.4049/jimmunol.178.5.2893
|View full text |Cite
|
Sign up to set email alerts
|

Induced SHIP Deficiency Expands Myeloid Regulatory Cells and Abrogates Graft-versus-Host Disease

Abstract: Graft-vs-host disease (GVHD) is the leading cause of treatment-related death in allogeneic bone marrow (BM) transplantation. Immunosuppressive strategies to control GVHD are only partially effective and often lead to life-threatening infections. We previously showed that engraftment of MHC-mismatched BM is enhanced and GVHD abrogated in recipients homozygous for a germline SHIP mutation. In this study, we report the development of a genetic model in which SHIP deficiency can be induced in adult mice. Using thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
74
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 64 publications
(84 citation statements)
references
References 43 publications
10
74
0
Order By: Relevance
“…However, the expansion of other immune cell types in vivo, such as myeloid-derived suppressor cells, likely also plays a role to suppress Th1 cell responses (37,46). Thus, as they become available, it will be very interesting to assess the DC phenotype and Th1/Th2 cell proclivity of DC-lineage specific SHIP knockout mice and to test the function of SHIP 2/2 DCs in vitro and in vivo in the absence of the influence of a pan-hematopoietic SHIP 2/2 milieu.…”
Section: /2mentioning
confidence: 99%
“…However, the expansion of other immune cell types in vivo, such as myeloid-derived suppressor cells, likely also plays a role to suppress Th1 cell responses (37,46). Thus, as they become available, it will be very interesting to assess the DC phenotype and Th1/Th2 cell proclivity of DC-lineage specific SHIP knockout mice and to test the function of SHIP 2/2 DCs in vitro and in vivo in the absence of the influence of a pan-hematopoietic SHIP 2/2 milieu.…”
Section: /2mentioning
confidence: 99%
“…We previously found that donor and host allogeneic responses are compromised in SH2 domaincontaining inositol 5-phosphatase (SHIP)-deficient hosts, which exhibit significantly reduced acute rejection of MHC-mismatched bone marrow grafts and GVHD. 6,7 Thus, an immunosuppressive environment prevails in SHIP-deficient hosts. We consistently observe a profound expansion of myeloid suppressor cells (MySC) in SHIP-deficient mice.…”
Section: Introductionmentioning
confidence: 99%
“…We consistently observe a profound expansion of myeloid suppressor cells (MySC) in SHIP-deficient mice. [6][7][8][9] Because host and donor T regs limit GVHD 4,10 and Mac1 ϩ Gr1 ϩ cells, similar to SHIP Ϫ/Ϫ MySC, expand T regs in tumor and GVHD models 11,12 ; we considered that the T reg compartment in SHIP-deficient hosts may also be expanded. In addition, SHIP deficiency could intrinsically effect T reg homeostasis and function.…”
mentioning
confidence: 99%
“…The expansion of myeloid progenitor cells in these chimeras is reminiscent of the myeloid-derived suppressor cells described in association with myelosuppression, GvHD, tumors and chronic infections 21,29 where they have been implicated in tumor-specific and nonspecific T-cell dysfunction. [30][31][32] Our earlier data, 21 and more recently those of others, 33 suggest that these cells may have a role in controlling GvH reactivity. Whether they contribute in this model to confining GvH reactivity to the lymphohematopoietic system is the subject of ongoing investigations.…”
Section: Discussionmentioning
confidence: 95%